Bilateral breast calciphylaxis in a patient who survived earlier extensive tissue necrosis 5 years previously: A case report. (2018) - Verstappen, E.M.J.; Maaskant-Braat, A.J.G.; Scheltinga, M.R.
Highlights: Consider calciphylaxis in patients with renal disease developing skin necrosis. A multidisciplinary treatment approach is recommended. The role of surgery and hyperbaric oxygen for tissue necrosis is limited. Abstract: Introduction: Calciphylaxis is a rare condition including patchy dermal necrosis that mostly affects chronic hemodialysis patients. The syndrome usually heralds impending death although patients may survive following a set of measures including an adapted dialysis regimen. The present case is a unique patient who recovered from an earlier episode of upper leg calciphylaxis 5 years previously but developed fatal bilateral breast necrosis. Presentation of case: A 69 year old Caucasian woman with a history of atrial fibrillation, hypertension, CVA, hyperparathyroidectomy for secondary hyperparathyroidism and end stage renal disease with hemodialysis recovered in 2012 from extensive symptomatic left upper leg necrosis due to calciphylaxis. In 2017, she developed painful, necrotic ulcers on both breasts, again due to calciphylaxis. She had no history of anticoagulants use but she did use prednisolone 5mg/day. She received adequate wound care, pain medication, antibiotics and dialysis frequency was increased with an addition of sodium thiosulfate. A bilateral ablation was discussed but she decided to stop all treatment following pulmonary aspiration and passed away one week later. Discussion: C alciphylaxis is a rare diagnosis that should be considered in patients with renal insufficiency developing painful patches of skin necrosis. Conclusion: A multidisciplinary treatment approach including hyperparathyroidectomy, modified hemodialysis and wound treatment is recommended. There is limited evidence for surgical intervention.